2018
DOI: 10.1111/1346-8138.14576
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of multiple basal cell carcinomas: The first study on Japanese patients

Abstract: Basal cell carcinoma (BCC), the most frequent skin cancer, has been increasing in incidence. However, the characteristics of multiple BCC have not been clarified in Japan. Therefore, we conducted a retrospective study to elucidate the features of multiple BCC compared with solitary BCC. The study population consisted of 327 patients with histopathologically proven BCC who were referred to the Department of Dermatology in Tottori University Hospital between November 2006 and April 2016. Of the 327 patients, 304… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(29 reference statements)
2
4
1
Order By: Relevance
“…In our study, we observed that older patients at a slightly higher male/female ratio comprised the group of mBCC as compared with the sBCC group (Table 2). This finding was in accordance with the previously published literature [8,9,22]. The distribution of histological subtypes of the tumor in both groups was similar and corresponded to the average of the incidence of various forms of the neoplasm [1] (Table S2).…”
Section: Solitary Versus Multiple Bccssupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, we observed that older patients at a slightly higher male/female ratio comprised the group of mBCC as compared with the sBCC group (Table 2). This finding was in accordance with the previously published literature [8,9,22]. The distribution of histological subtypes of the tumor in both groups was similar and corresponded to the average of the incidence of various forms of the neoplasm [1] (Table S2).…”
Section: Solitary Versus Multiple Bccssupporting
confidence: 91%
“…Multiple BCC patient risk factors (e.g., sex, age, etc.) have been investigated in the literature [7][8][9][10]. Further studies on the clinical features of multiple tumors and patients' profiling could provide physicians with important knowledge towards prevention of this neoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Van Lersel et al 12 and Ramachandran et al 13 reported that males older than 60 years old were at an increased risk of multiple BCCs. Adachi et al 2 compared clinicopathological data in a study of 327 cases with solitary and multiple tumors. No gender variation was found between the two groups, but there was a statistically significant difference in the incidence rate of multiple BCCs in our study, occurring more frequently in males and older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Basal cell carcinoma (BCC) is the most common type of cancer worldwide, and its occurrence is inversely related to a country’s geographical latitude 1 . BCC is most frequently seen in light-skinned people, generally as a solitary lesion, although it can also develop as multiple lesions 2 . The risk of different tumor formations is high in patients with two or more BCCs 1 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature data, the percentage of patients with more than 1 primary BCC lesion has varied from 7% to 46% [3,[6][7][8][9][10][11][12][13] and the mean number of tumors per individual has ranged from 1.5 to 1.9. [11,14] This variability may be explained by several factors, such as the total number of participants, distinct ethnicity, different follow-up periods, and misclassification bias.…”
Section: Prevalence Of Multiple Bcc Casesmentioning
confidence: 99%